Pengaruh Online Customer Review dan Promosi Gratis Ongkir Terhadap Keputusan Pembelian Produk Kosmetik di Aplikasi Shopee bagi Generasi Z - Kurniawan, Kevin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of increasingly modern technology causes consumer behavior to like shopping online. The formulation of the problem in this research is how influence Online Customer Reviews and free shipping promotions have on the decision to purchase cosmetic products on the Shopee application for UKMC students in Palembang. One of the features that is popular when shopping online is the Free Shipping Promo, as well as Online Customer Reviews as support for seeing reviews of previous buyers. The aim of this research is to test whether there is an influence of free shipping promotions and Online Customer Reviews on purchasing decisions for cosmetic products on the Shopee marketplace. Respondents in this study were 42 respondents. Based on the research results, it can be seen that: (1) Online Customer Reviews have no significant effect on purchasing decisions (2) Free shipping promotions have a significant positive effect on purchasing decisions (3) Online Customer Reviews and free shipping promotions simultaneously have a significant effect on purchasing decisions